The UBS-SBC Merger and Competition in the Swiss Retail Banking Sector - Dominik Egli; Bertrand Rime (Swiss National Bank, Study Center Gerzensee, 1999)
We address two questions about the impact of the UBS-SBC merger: (i) How will the concentration in the Swiss retail banking market change, and (ii) what are the expected consequences for the consumers. The answer to the first question is based on a comparison of Herfindahl and C3-indices in 1997 as they actually have been to as they could have been if the banks already had been merged. For both types of indices, and for the two product groups considered (loans and mortgages, savings deposits) the impact of the merger is huge. To answer the second question, we have examined how concentration interfered with savings deposits and mortgages interest rates in the previous decade, between the cantons and over time. The results obtained for savings deposits indicate that the structure performance hypothesis dominates for large cantons, while the efficiency hypothesis and the contestable market hypotheses cannot be rejected for small cantons. For mortgages, the contestable market hypotheses clearly dominates for large cantons, while for small cantons evidence is split between the efficiency hypothesis and the contestable market hypothesis.
Keywords: 330